2015
DOI: 10.1093/europace/euv079
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the new risk prediction model (HCM Risk-SCD) and classic risk factors for sudden death in patients with hypertrophic cardiomyopathy and defibrillator

Abstract: During an average follow-up of 4 years, 16.67% presented appropriate events (4.16%/year). HCM Risk-SCD predicted the onset of events more suitably than classic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…Similarly, inappropriate shocks occurred at a rate of 4.9% (95% CI: 3.9-6.0) per year (I 2 =75%) ( Figure 3). Among six studies (7,8,10,25,29,33), heart transplant was required in 1.6% of patients per year. The annual incidence of lead malfunction and lead displacement was 1.4% (95% CI: 0.8-2.5) and 1.3% (95% CI: 0.8-2.0) respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, inappropriate shocks occurred at a rate of 4.9% (95% CI: 3.9-6.0) per year (I 2 =75%) ( Figure 3). Among six studies (7,8,10,25,29,33), heart transplant was required in 1.6% of patients per year. The annual incidence of lead malfunction and lead displacement was 1.4% (95% CI: 0.8-2.5) and 1.3% (95% CI: 0.8-2.0) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The model predicts that one SCD will be prevented every 5 years if 16 patients with a 5-year risk of SCD that is greater than or equal to 4% are given ICD therapy (45). Validation studies have suggested that the new model is superior to traditional models based on bivariate risk factors (29,46). Future studies into the role of cardiac magnetic resonance imaging may further improve the current risk models.…”
Section: Discussionmentioning
confidence: 99%
“…Validation studies have suggested that the new model is superior to traditional models based on bivariate risk factors 31,32 , and current clinical practice guidelines 33 , has included the HCM Risk-SCD model on their recommendations of prevention of sudden cardiac death as a method of estimating risk of SCD at 5 years in primary prevention ( Figure 7 ).…”
Section: Evidence Of Icd In Hcmmentioning
confidence: 99%
“…Las recomendaciones de implante de DAI están basadas en estudios observacionales, retrospectivos y de cohorte que miden la asociación de ciertas características clínicas con el pronóstico (5) . Esta situación nos plantea una clara diferencia con las recomendaciones para prevención primaria de MSC en las miocardiopatías isquémica y dilatada, donde la indicación de DAI está basada en estudios clínicos randomizados prospectivos que le confieren una evidencia más sólida (33)(34)(35) .…”
Section: Modelos Para Estimar Muerte Súbita Cardíacaunclassified